Semiotika Riffaterre untuk “Elegi Laut” Sofyan Daud - Naratungga Indit Prahasita (Kantor Bahasa Provinsi Maluku Utara, 2016)
This study aims to describe the meaning of poem ‘Elegi Laut’ written by Sofyan Daud based on Riffaterre’s semiotic approach. The method used on this study is a qualitative method through heuristic and hermeneutic reading techniques. The result of this study shows that the poem of Sofyan Daud’s ‘Elegi Laut’ worked using literary conventions (indirectness), change of meaning (displacing) in the form of metaphor, and creating of meaning in the form of homologues 'common sense' and the strengthening of meaning. The variants refer to the same matrix, ie human beings as the actor of ecological imbalance itself. The matrix of Elegi Laut brings this poem to a textual hipogram as in Mangunwijaya work’s Ikan-Ikan Hiu, Ido, Homa